An indigenous artificial larynx - Vijay A Shah; Ashok Raje; Pradeep Wagh (Journal of All India Institute of Speech and Hearing, 1970)
Usually laryngectomised patients are advised by their surgeons and speech therapists to learn Esophageal Speech. However not all laryngectomees can master esophageal speech. An alternative is to use an artificial larynx